How Does Fiscal Policy Affect Bank Credit? Evidence from China - Huan Yan; Weiguo Xiao; Qi Deng; Sisi Xiong (Discrete Dynamics in Nature and Society)
Using a set of Chinese economic data and a structural vector autoregression (SVAR) model, this paper investigates the transmission channels of fiscal policy to bank credit in China. We find that increases in tax revenue can increase bank credit through external financing premium channel, collateral channel, and bank liquidity channel. We also find that increases in government spending can reduce bank credit through bank liquidity channel and increase bank credit through external financing premium channel and collateral channel.